خطة التدريس لمادة الترجمة في المدرسة الثانوية الحكومية دولوفو ماديون - Bagas Mukti Nasrowi (Universitas Yudharta Pasuruan, 2019)
Translation is the ability to transfer speech either literally or by acting from one language to another without increasing or decreasing in such a way that the reader or the hearer understands the translated text as understood by the original text reader or the listener. The translation into the various literature dealing with the theory of translation is divided into two main types: literal translation and free translation. The researcher takes the subject of “the plan to study translation in Senior High School Dolopo Madiun” because some students in the Senior High School have difficulty in understanding the text Arabic language and made it difficult for students to translate the Arabic language into the Indonesian language. Teaching plans for translation include: teaching objectives for the subject of translation, content for translation material, teaching methods for translation, means of translation and evaluation of translation material.